Modeling Arbitrator Delay-Area Dependencies in Customizable Instruction Set Processors - Zarar, Shuayb; Lam, Siew-Kei; Srikanthan, Thambipillai (IEEE Int. Workshop on Electronic Design, Test and Applications (DELTA), 2006)
Instruction set customization is becoming a preferred approach for accelerating high-speed demanding applications. In this paper, we present performance and delay-area product estimation models to accelerate the design of custom instructions on the NIOS-II configurable processor platform. The proposed models outline the performance bandwidth and delay-area product to enable profitable selection on the type and number of custom instructions, without the need to undertake time-consuming hardware synthesis in the design exploration stage. The models exhibit a high degree of accuracy as they incorporate the architectural dependencies of the arbitrator logic between the Nios II processor and custom hardware. Experimental results reveal that the area-time implications of the arbitrator logic with respect to the number of custom instructions can significantly affect the system's performance and area utilization.